Revolusi Kopernikus: Nilai & Pengaruhnya Dalam Epistemologi Obyektivistis - Valentinus . (Studia Philosophica et Theologica, 2002)
Delving into epistemology, one must recognize the “scientists” behind the revolutionary philosophical perspective of modern science. One of the most well known scientists was Copernicus. He could not indeed be categorized as epistemologist in the strict sense, rather he was a scientist. Yet what he discovered has changed the paradigm of not mere scientific perspective that the helios is the true center of the universe, not the earth, but also of human comprehensive point of philosophical view. When it was the earth that had been believed so long time as the center of the universe, the human being remained the pivotal point of thinking; but once the empiric science of Copernicus observed that it was not the earth, the new paradigm came out. The human being is only a particle of the very huge and sophisticated system of the universe. What would be the center is not as clear as before. The universe itself seems to be the center. This article studys the impact of the Copernican revolution of science to epistemology which in turn changes the human being’s philosophical perspective toward his/her life world.